Hubungan Antara Status Gizi Dan Tingkat Stres Dengan Kejadian Siklus Menstruasi Tidak Normal Pada Remaja Putri Di Pondok Pesantren Assa’adah Depok Tahun 2023 - Ikhtiani, Nabila; Asiah, Nur (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2023)
Adolescence is a transition period from children to adults who experience the changes of maturity, one of which is the menstruation. Factors that affect the menstrual cycle include nutritional status and stress levels. This study aims to determine the correlation between nutritional status and stress levels on the menstrual cycle in young women at the Assa'Adah Depok Islamic Boarding School. This study uses a cross sectional design with the population and the sample to be studied are all female students who have experienced menstruation totaling 60 students. The sampling technique used saturated sampling. Data collected in the form of length of menstrual cycle, nutritional status, and stress level. Data were collected by filling out questionnaires and anthropometric measurements. Analyzed by univariate and bivariate. The results of this study showed that there were 68.3% of female students who experienced abnormal menstrual cycles, 56.7% abnormal nutritional status, and 85% severe stress levels. In the Chi Square statistical test results that there is a significant relationship between nutritional status (p value = 0.003) and stress level (p value = 0.023) on the menstrual cycle of young women. It is expected that the Yayasan can provide education related to the menstrual cycle and its disorders, provide intake according to balanced nutrition, and provide counseling guidance.